Sequential effects in facial attractiveness judgments: Separating perceptual and response biases. Issue 10 (26th November 2021) - Kramer, Robin S. S.; Pustelnik, Lyndsay R.
ABSTRACT: When items are presented sequentially, the evaluation of the current item is biased by both the previous item's value (perceptual bias) and the previous response given (response bias). While these biases have been identified in judgements of facial attractiveness, it is unclear as to whether they produce assimilation and/or contrast effects. Here, two tasks were employed to measure each bias in isolation. By presenting a preceding face without collecting a response, perceptual biases could be investigated, while response biases were considered by requesting a preceding response without presenting a face. Our results demonstrated a perceptual bias in which attractiveness ratings given to the current face shifted away from the baseline attractiveness value of the previous face, while we found no evidence of a response bias due to the previously selected value. These findings highlight the utility in considering sequential biases separately when trying to determine the nature of these effects.